2006
DOI: 10.1021/es061160z
|View full text |Cite
|
Sign up to set email alerts
|

Arsenate and Arsenite Adsorption and Desorption Behavior on Coprecipitated Aluminum:Iron Hydroxides

Abstract: Although arsenic adsorption/desorption behavior on aluminum and iron (oxyhydr)oxides has been extensively studied, little is known about arsenic adsorption/desorption behavior by bimetal Al:Fe hydroxides. In this study, influence of the Al:Fe molar ratio, pH, and counterion (Ca2+ versus Na+) on arsenic adsorption/desorption by preformed coprecipitated Al:Fe hydroxides was investigated. Adsorbents were formed by initial hydrolysis of mixed Al3+/ Fe3+ salts to form coprecipitated Al:Fe hydroxide products. At Al:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
181
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 353 publications
(197 citation statements)
references
References 20 publications
14
181
1
1
Order By: Relevance
“…that allophane has a strong affinity for As(V) and supports the fact that arsenic mobility in soils is limited by its capacity to be sorbed on soil components particularly by metal oxides, short-ranged ordered aluminosilicates [25] and Al and Fe hydroxides [26].…”
Section: The Large Reduction Of As(v) Concentration After 24 Hours Ofsupporting
confidence: 55%
“…that allophane has a strong affinity for As(V) and supports the fact that arsenic mobility in soils is limited by its capacity to be sorbed on soil components particularly by metal oxides, short-ranged ordered aluminosilicates [25] and Al and Fe hydroxides [26].…”
Section: The Large Reduction Of As(v) Concentration After 24 Hours Ofsupporting
confidence: 55%
“…Hu et al (2015a) studied the interference of Ca toward As(V) molecular structures absorbed on TiO 2 , and the results suggested the formation of a Ca-As(V)-TiO 2 ternary surface complex. The formation of a ternary complex can significantly increase the synergetic uptake of As(V) and Ca (Masue et al, 2007), and promote As attenuation in groundwater (Zhang et al, 2014). Though the coexisting Mg concentration (104.3 mg/L) was much higher than Ca (39.1 mg/L) in groundwater, the Ca adsorption density was higher than Mg (311 mg/g vs. 171 mg/g) in a study by Cui et al (2015a).…”
Section: Coexisting Ions In Geogenic Groundwatermentioning
confidence: 91%
“…The As(III) inner-and outer-sphere adsorption coexists, whereas for As(V), inner-sphere complexes are predominant [123]. Chemical models also confirmed that arsenate adsorption occurs over a pH range of 4.5 to 9 on gibbsite and amorphous Al hydroxide [51,118]. The degree of crystallinity of Al oxides and hydroxides also is important for As adsorption.…”
Section: Arsenic Adsorption On Aluminum Oxidesmentioning
confidence: 82%
“…One of the most important key parameters that may affect the adsorption of As(III) and As(V) is pH. The greatest adsorption of As(V) usually occurs at low pH values (pH 3-6) and decreases with increasing pH (pH >6) [118,119]. Greater adsorption of As(V) at low pH is attributable to more favorable adsorption energies between the more positively charged surface and negatively charged H 2 AsO 4 − , which is the predominant As(V) species between pH 2 and 6.…”
Section: Arsenic Adsorption On Iron Oxidesmentioning
confidence: 99%